2018
DOI: 10.1111/mcn.12619
|View full text |Cite
|
Sign up to set email alerts
|

Low level aflatoxin exposure associated with greater linear growth in southern Mexico: A longitudinal study

Abstract: Aflatoxins are a group of naturally occurring mycotoxins, which can lead to death and are a known cause of hepatocellular carcinoma. AF exposure has been hypothesised to lead to stunted growth in children, but separating the AF effect from other determinants of linear growth retardation is difficult. The study used secondary data from an efficacy trial conducted in young children in southern Mexico to test the comparative efficacy of a milk-based multiple micronutrient-fortified food, a multiple micronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
1
33
2
Order By: Relevance
“…However, sample preparation for this technique is time-consuming [70]. Liquid chromatography coupled with fluorescence detection (LC-FLD) was used frequently (24% of the methods reviewed) [54,55,57,58,81,[85][86][87][88][89][90][91][92].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
See 2 more Smart Citations
“…However, sample preparation for this technique is time-consuming [70]. Liquid chromatography coupled with fluorescence detection (LC-FLD) was used frequently (24% of the methods reviewed) [54,55,57,58,81,[85][86][87][88][89][90][91][92].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
“…To release AFB1-lysine (AFB1-lys) adduct from albumin, proteins in serum samples are digested with Pronase ® for a few hours at 37 • C. AFB1-lys is then extracted and purified with SPE by means of a mixed-mode anion exchange reversed-phase matrix. Next, the analytes are eluted, mainly through the use of methanol (MeOH) with formic acid, then concentrated and reconstituted in the mobile phase before analysis with LC-MS/MS [49,65,81,83,87,[112][113][114][115], LC-FLD [81,[88][89][90][91][92] or ELISA [73][74][75][76][77][78][79]117]. McCoy et al (2008) [70] and Scholl et al (2006) [123] reported good correlations of the concentration levels obtained from ELISA, LC-FLD and LC-MS.…”
Section: Mycotoxin Biomarkers In Human Blood Plasma and Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in emerging and developing nations, most contaminated crops enter the food and feed chains, regardless of their aflatoxin content [3,[20][21][22][23][24][25]. The absence of mechanisms to enforce aflatoxin tolerance levels results in chronic aflatoxin exposure with subsequent lack of access to markets, poverty, low well-being, poor economic growth, being among other constraints in the affected populations [2,26,27]. For all these reasons, in the developing world, contamination of food and feeds with aflatoxins has a profound negative impact on personal, social, and national development opportunities.…”
Section: The Aflatoxin Problemmentioning
confidence: 99%
“…These results suggest that low levels of aflatoxin may not contribute to growth impairment in this sample, though fumonisin may play a role (Chen et al, ). Leroy et al found that low‐level aflatoxin exposure (median level = 0.82 pg/mg) was actually associated with greater linear growth in a longitudinal study of infants in southern Mexico (Leroy, Sununtnasuk, García‐Guerra, & Wang, ). Lastly, a recent study using a maternal and newborn cohort in Nepal found that relatively low maternal aflatoxin exposure was associated with a slight increased risk of being small for gestational age but not with birth weight, birth length, anthropometric z‐scores, low birthweight, stunting, or preterm birth (Andrews‐Trevino et al, ).…”
Section: Discussionmentioning
confidence: 99%